PENDETEKSIAN KESALAHAN KETIK DENGAN DAMERAU-LEVENSHTEIN DISTANCE DAN TRIE - James Tirta Halim; Lely Hiryanto; Irvan Lewenusa (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Typographical errors are commonly found in text. Many applications implement a spell checking feature to detect and correct typographical errors. Spell checking requires an algorithm to calculate the similarity of two strings. This study compares Damerau-Levenshtein Distance and Trie in checking and correcting typographical errors in the names of function calls in source code based on the processing time and accuracy of the spelling correction. Accuracy is calculated by classifying the results of the spelling correction in a Confusion Matrix. This study shows that Trie is faster than Damerau-Levenshtein Distance, in which Trie’s processing time took 10.07% of Damerau-Levenshtein Distance’s. However, Damerau-Levenshtein Distance can correct more types of typographical errors than Trie, yielding an accuracy of 89.7% compared to 45.71%.